Support from Health Workers for the Participation of Mothers and Babies for Immunization at Posyandu Tulif, Cempaga Hulu District, East Kotawaringin Regency - Riza Tsalatsatul Mufida,; Miftakhur Rohmah,; Deonesia Pramita, (Journal of Health Science Community, 2024)
Maintaining the health of infants can be done by preventing and improving health through immunization. support from health workers has a role in increasing the willingness of mothers of babies/toddlers to be immunized by empowering posyandu. The aim of this research is to analyze the effect of support from health workers on mothers' participation in immunization at Posyandu Tulif, Cempaga Hulu District, East Kotawaringin Regency. This research uses a correlational analytical design with a cross-sectional approach. The samples in this study were mothers who had 1 year old babies at Posyandu Tulif, Cempaga Hulu District, East Kotawaringin Regency in June 2022, totaling 32 respondents. Sampling in this study used simple random sampling technique. Data collection using questionnaires. Data analysis to see the relationship between the independent variable and the dependent variable used the chi square statistical test with a significance level of α = 0.05. The research results showed that of the 32 respondents, the majority of respondents received good health support, namely 21 respondents (65.7 %) and the majority of respondents actively participated in carrying out immunization, namely 20 respondents (62.5%). The results of data analysis using the chi square statistical test showed that the P value was < α 0.05 (0.000 < 0.05), which means that there was an influence of support from health workers on the participation of mothers in babies for immunization at Posyandu Tulif, Cempaga Hulu District, East Kotawaringin Regency. Good health will influence the mother's participation in immunization at the posyandu.